2019
DOI: 10.1186/s12263-019-0643-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of continuous high temperature affecting growth performance, meat quality, and muscle biochemical properties of finishing pigs

Abstract: Background The mechanism of high ambient temperature affecting meat quality is not clear till now. This study investigated the effect of high ambient temperature on meat quality and nutrition metabolism in finishing pigs. Methods All pigs received the same corn-soybean meal diet. A total of 24 Landrace × Large White pigs (60 kg BW, all were female) were assigned to three groups: 22AL (fed ad libitum at 22 °C), 35AL (ad libitum fed at 35 °C), and 22PF (at 22 °C, but fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
(47 reference statements)
2
13
1
Order By: Relevance
“…At thermoneutral conditions, the reduced intake had a negative effect on the IMF level of muscles of Iberian pigs, while the heat stress had a positive effect at the same intake level, thus counteracting the decrease due to the lower feed consumption and restoring the IMF level to values observed in TN ad libitum fed pigs. This finding is no consistent with previous studies in conventional porcine breeds that have shown that both feed restriction and exposure to high temperature reduced IMF deposition [12,13]. In lean pigs the effect of high temperature on IMF content was mainly explained by the decreased feed intake [29,30].…”
Section: Chemical Composition and Fa Profile Of Musclessupporting
confidence: 72%
See 1 more Smart Citation
“…At thermoneutral conditions, the reduced intake had a negative effect on the IMF level of muscles of Iberian pigs, while the heat stress had a positive effect at the same intake level, thus counteracting the decrease due to the lower feed consumption and restoring the IMF level to values observed in TN ad libitum fed pigs. This finding is no consistent with previous studies in conventional porcine breeds that have shown that both feed restriction and exposure to high temperature reduced IMF deposition [12,13]. In lean pigs the effect of high temperature on IMF content was mainly explained by the decreased feed intake [29,30].…”
Section: Chemical Composition and Fa Profile Of Musclessupporting
confidence: 72%
“…This impact has been associated with increased oxidative reactions and production of reactive oxygen species (ROS) thus disrupting the redox balance that ensures the stability in skeletal muscle and preserve the meat quality [ 10 , 11 ]. Compositional changes of meat such as decreased intramuscular fat (IMF) have also been reported as a result of high temperature exposition [ 12 , 13 ]. Traditionally, these changes have been related to decreases of feed intake, but certain studies have shown that heat stress per se may also reduce metabolic rate and alter oxidative metabolism in muscle to reduce thermogenesis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the immunity and cell adhesion-related signaling pathways, it is worth noting that the Lipin1, Sestrin1 (SESN1) and fibroblast growth factor receptor 2 (FGFR2) genes of the DEGs are associated with protein synthesis and lipid metabolic process, which also contribute to the muscle growth. As known, the Lipin1 gene has an important regulatory role in lipolysis and reducing fat accumulation (40). The regulation of Lipin1 gene expression in lipid metabolism is accompanied by alteration of the protein synthesis process (41).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, it may be characterised that heat causes changes of gene expression, leads to oxidative damage and changes the intracellular signal transduction [ 40 , 41 ]. The recent study of Ma et al [ 42 ] using transcriptone analysis of the longissimus dorsi showed that heat load causes downregulation of the gene involved in muscle structure and development, energy and catabolic metabolism. In turn, it upregulates genes mainly involved in DNA or protein damage/recombination, or processes of cell cycle, biogenesis and stress and immune responses.…”
Section: Thermoregulation Behavioural and Physiological Changes Imentioning
confidence: 99%